(untitled) (Global Journal of Human-Social Science, 2014)
Slums are known as culture of poverty. Thus there is lack of proper shelter, lack of basic requirements such as clean air, clean water, suitable toilets, and electricity. Lack of proper diet affects many, especially the growing children, lack of medical facilities result in spread of diseases, leading to ill health and loss of man-powers, lack of transport results in longer commuting times and longer hours to reach essential destinations. The concept of a slum varies widely from country to country and depends on a variety of defining parameters. Sometimes slums are used interchangeably with squatters. In general, it is considered as a residential area in urban vicinity inhabited by the very deprived who have no access to tenured land of their own, and hence ’squat’ on vacant land, either private or public.